2003
DOI: 10.1002/j.2161-1912.2003.tb00525.x
|View full text |Cite
|
Sign up to set email alerts
|

First Annual Diversity Challenge: “How to Survive Teaching Courses on Race and Culture”

Abstract: The authors discuss the highlights of the 1st annual Diversity Challenge held October 11–12, 2001, at Boston College, Boston, MA. The Challenge's general focus was preparing educators to cope with the resistances encountered when they teach about race and ethnic culture. This introduction (a) provides an overview of the proceedings, (b) summarizes themes of presentations and articles selected, and (c) offers recommendations for subsequent events. Los autores analizan el primer Reto de Diversidad, que tuvo luga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…When reviewing the results from this study, a few notable pattems exist. Despite reports that multicultural courses are often very challenging to teach (Carter, 2003;Helms et al, 2003), the majority of the faculty members in this study believe that students respond positively to the course and to them as professors. This belief is somewhat tempered by some qualitative responses describing negative treatment or attitudes from students, but overall most faculty reported that their multicultural counseling course is positively received.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…When reviewing the results from this study, a few notable pattems exist. Despite reports that multicultural courses are often very challenging to teach (Carter, 2003;Helms et al, 2003), the majority of the faculty members in this study believe that students respond positively to the course and to them as professors. This belief is somewhat tempered by some qualitative responses describing negative treatment or attitudes from students, but overall most faculty reported that their multicultural counseling course is positively received.…”
Section: Discussionmentioning
confidence: 75%
“…Despite the increased availability of diverse teaching strategies and philosophies, many faculty members who teach multicultural counseling courses still face unique educational challenges (Gloria, Riekmann, & Rush, 2000;Helms et al, 2003;Jackson, 1999), and while these challenges may be discussed informally or at professional conferences they are rarely researched.…”
mentioning
confidence: 99%
“…However, when it came to teaching a multicultural course in the program, despite faculty members' commitment to social justice and multiculturalism, I was warned of student resistance and challenges. In fact, my major mentor in the field, a leading worldwide African American scholar, advised me not to teach a multicultural course until I received tenure, as research consistently has suggested that teaching racially loaded coursework can influence the tenure process (e.g., Helms et al, 2003;.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that increasing awareness involves intangible outcomes, such as attitudinal change, makes it difficult to measure and difficult to set as a training goal (Ridley, Mendoza, & Kanitz, 1994). There is a great deal of variance in the pedagogical efforts to achieve this goal (Helms et al, 2003;Ridley et al, 1994). Reaction papers, journal writing, role playing, videotaping, cross-cultural immersion experiences, cross-cultural simulation experiences, experiential exercises, fishbowl exercises, small-group processing, and focus groups are a few of the interventions discussed in the counseling literature (see Helms et al, 2003;Pope-Davis & Coleman, 1997).…”
Section: Challenges In Training For Multicultural Awarenessmentioning
confidence: 99%
“…There is a great deal of variance in the pedagogical efforts to achieve this goal (Helms et al, 2003;Ridley et al, 1994). Reaction papers, journal writing, role playing, videotaping, cross-cultural immersion experiences, cross-cultural simulation experiences, experiential exercises, fishbowl exercises, small-group processing, and focus groups are a few of the interventions discussed in the counseling literature (see Helms et al, 2003;Pope-Davis & Coleman, 1997). This literature suggests that these efforts are meeting with some success and that, in programs across the country, students are grappling with issues of race and culture and growing as a result (Helms et al, 2003).…”
Section: Challenges In Training For Multicultural Awarenessmentioning
confidence: 99%